Analysis of Communication Barriers for Emergency Department Staff in Providing Information to Patients and Service Units at Dr. Pirngadi Regional Hospital, Medan - Nurhayati, Nurhayati; Winanti, Sumi Fitri; Ramadani, Rani; Nasution, Amanda Dwika (PROMOTOR, 2025)
Communication is an essential aspect of health services, as it plays a key role in delivering information to both healthcare personnel and patients. In hospitals, the Emergency Registration Unit (ERU) or the patient registration counter in the Emergency Department (ED) serves as the primary entry point for emergency patients to receive care. ERU officers are responsible for performing initial administrative procedures, recording patient identity, coordinating with medical staff, and conveying important information to patients’ families and related service units. This study employed a descriptive qualitative approach to examine communication barriers experienced by ERU officers in the Emergency Department of Dr. Pirngadi General Hospital, Medan, when delivering information to patients and service units. The findings revealed several communication barriers, including suboptimal effectiveness in explaining emergency procedures, delayed inter-unit coordination despite the use of a computerized information system, and limited interpersonal communication skills among officers under high work pressure. In addition, patients’ and families’ lack of understanding of service procedures often led to misperceptions of the information provided. The study highlights the importance of interpersonal and empathic communication training, as well as the optimization of information systems to improve the quality of communication and services in the Emergency Department. Data validity was ensured through triangulation and member checking, and the study received official approval from the hospital management.